Αvβ3 Integrin and tumour blood vessels — learning from the past to shape the future. (October 2016) - Demircioglu, Fevzi; Hodivala-Dilke, Kairbaan
Highlights: Targeting the ectodomain of αvβ3 integrin can control tumour blood vessel development. Facing the problems of targeting the integrin ectodomain. Thinking about integrin endocytosis and targeting cytotail adhesome interactions. Abstract : Angiogenesis, the formation of new blood vessels from pre-existing ones, is thought to enhance tumour growth and these blood vessels can act as conduits of tumour cell metastasis. Integrins, the family of cell surface extracellular matrix receptors, can promote endothelial cell migration and survival, both essential features of angiogenesis, and were thus considered good targets for anti-angiogenic therapy. This sparked the development of agents to block integrin function as new cancer therapies. Here, we review the current status of αvβ3-integrin in tumour angiogenesis. Learning from what we now know about integrin conformational changes and endocytosis, we discuss the possible future of targeting blood vessel αvβ3-integrin in the control of cancer.